Biomimetically Engineered Demi‐Bacteria Potentiate Vaccination against Cancer. Issue 10 (15th June 2017) - Ni, Dezhi; Qing, Shuang; Ding, Hui; Yue, Hua; Yu, Di; Wang, Shuang; Luo, Nana; Su, Zhiguo; Wei, Wei; Ma, Guanghui
Abstract: Failure in enhancing antigen immunogenicity has limited the development of cancer vaccine. Inspired by effective immune responses toward microorganisms, demi‐bacteria (DB) from Bacillus are engineered as carriers for cancer vaccines. The explored hydrothermal treatment enables the Bacillus to preserve optimal pathogen morphology with intrinsic mannose receptor agonist. Meanwhile, the treated Bacillus can be further endowed with ideal hollow/porous structure for efficient accommodation of antigen and adjuvant, such as CpG. Therefore, this optimal engineered nanoarchitecture allows multiple immunostimulatory elements integrate in a pattern closely resembling that of bacterial pathogens. Such pathogen mimicry greatly enhances antigen uptake and cross‐presentation, resulting in stronger immune activation suitable for cancer vaccines. Indeed, DB‐based biomimetic vaccination in mice induces synergistic cellular and humoral immune responses, achieving potent therapeutic and preventive effects against cancer. Application of microorganism‐sourced materials thus presents new opportunities for potent cancer therapy. Abstract : A demi‐bacteria (DB)‐based vaccine platform is developed through hydrothermal engineering of bacillus . Such constructed biomimetic vaccine with multiple pathogen‐like features greatly enhances antigen uptake and cross‐presentation, resulting in stronger immune activation. Indeed, DB‐based biomimetic vaccine induces synergistic cellular and humoral immune responses, achieving potent therapeutic and preventive effects against cancer.